THE APPLICATION PROGRAM OF THE PREPARATION OF THE SYLLABUS AND LEARNING IMPLEMENTATION PLAN (RPP) 2013 CURRICULUM ON TEACHERS MADRASAH IBTIDAIYAH - Surur, Agus Miftakus; Rais, Pandi; Habib, Habib (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Application of 2013 (K13) curriculum in the educational world Indonesia was able to "require" teachers to improve performance in carrying out activities of teaching and learning. The study will be carried out contained in the syllabus and detailed in the plan of implementation of the learning (RPP). The syllabus and the RPP should be drawn up in such a way so that it is based on the guidelines so that learning will get results as planned. The preparation of the syllabus and the RPP became very important because it led to a proper learning. The right plan will produce a quality learning. So that teachers can craft a syllabus and RPP easily need Congressional program to compose it. The program is able to help the teacher in drawing up the syllabus and RPP in accordance with needs. The program is easy to implement because the process is entering a time in accordance with the categories, but capable of producing the syllabus and RPP altogether.